IMPLEMENTASI METODE TARTIL DAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN BACA TULIS MENGHAFAL DAN MENGARTIKAN AL-QURAN - Nurlisma Nurlisma (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The Qur'an is a way of life for humans, especially believers, not only as a guide and guide to life, the Qur'an is also a syifa' (medicine, healer, parrot (explanatory), and Al-Furqan (differentiation between right and wrong). Therefore, it is not surprising that the Qur'an contains many virtues and majesty. Someone who always interacts with the Qur'an is by believing in it, applying tajwid and makhraj in reading it, listening to it, memorizing it, understanding its meaning, or practicing it by making it a guide and proof in life, then he will get the virtue and glory with Allah both in the world and in the hereafter. Reading the Qur'an aims to improve the ability to read the Qur'an properly and correctly for Muslims in order to improve and appreciate and experience the Qur'an. in everyday life, and reading the Qur'an can also be directed to children from an early age so that children can read, understand what has been learned. stated by the Qur'an and trying to apply it in life. Increasing the reading of the Qur'an is a must to make it easier for students to memorize, and understand the holy verses of the Qur'an itself as well as make it easier for students to write verses of the Qur'an. -The Qur'an is in accordance with the actual letters, to make it easier for students to master reading, memorizing, writing and understanding the Qur'an, this can be done by approaching/using the right methods and media.